(untitled) (Proceedings of the International Conference on Education, 2019)
Life skills learning is one of the learning processes where students learn various concepts and apply them in daily life. In the process of learning, students are faced with certain situations so that they get a new learning experience perceived benefits. The objective of this research was: 1) to know the mastery of academic and social life skills in practice of making alum from waste can, 2) to know the motivation of students in the implementation of the practice of making alum from waste can, 3) know the concept mastery aspect in the implementation of the practice of making alum of waste can. This research is a quasi-experiment with one-group posttest study design. Research subjects were students of Chemistry Education Department who take inorganic chemistry experiment. Instruments used were observation sheet and rubric indicator of work assessment (for academic and social life skill) and questionnaire (for motivation), and subjective test: pre-test and post-test (for conceptualization). The research data was analyzed by qualitative descriptive analysis technique, that is by calculating the average of every aspect that is assessed and converting it into qualitative criteria. Based on the result of research indicated that student’s motivation in practice gets good category while the value of mastery of academic skill and social life skill was in good category and mastery of concept got very good category.